Business cycles with cyclical returns to scale - Jay Hyun; Ryan Kim; Byoungchan Lee (Osaka University, Institute of Social and Economic Research (ISER), 2022)
We study business cycles with cyclical returns to scale. Contrary to tightly parameterized production functions (Cobb-Douglas and Constant Elasticity of Substitution), we empirically identify strong input complementarity that leads to procyclical returns to scale. We therefore propose a flexible translog production function that allows complementarity-induced procyclical returns to scale, and we integrate this function into a standard medium-scale dynamic stochastic general equilibrium (DSGE) model. The estimated model with the procyclical returns to scale (i) features procyclical price markups, (ii) better matches the cyclicality of factor shares, and (iii) decreases by nearly half the contribution of markup shocks to output fluctuations.
Keywords: C11; E23; E31; E32; 330; Business cycles; Translog production function; DSGE model; Returns to scale; Markup; Markup shocks